The Effectiveness of Iaic (I'm Aware I Care) Method Education Based on the Health Belief Model on HIV/AIDS Prevention Behavior in Adolescents At SMA Negeri 1 Telaga - Fitriani Tolinggi; Irwan; Reinaldi Julfirman Saleh (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Adolescents are a vulnerable group to HIV/AIDS transmission due to risky behaviors and lack of proper knowledge and understanding of HIV/AIDS prevention. One of the prevention efforts that can be done is through health education using audiovisual media. This study aims to determine the differences in HIV/AIDS prevention behavior in adolescents before and after being educated with the IAIC (I'm Aware I Care) method at SMA Negeri 1 Telaga. This study uses a quasi-experimental design with a one group pretest-posttest design. The research sample amounted to 186 respondents who were taken using random sampling techniques. Data analysis was carried out using the Paired Sample t-test. The results of the study showed an increase in HIV/AIDS prevention behavior in adolescents after being educated on the IAIC method. The results of the statistical test obtained a p-value of 0.000 (p < 0.05), which shows that the education of the IAIC (I'm Aware I Care) method based on the Health Belief Model is effective in HIV/AIDS prevention behavior in adolescents at SMA Negeri 1 Telaga. It is recommended that students are expected to increase knowledge, awareness and positive attitudes on HIV/AIDS prevention by utilizing audiovisual media and applying it in daily life.